Allocation of Salamandra auriculata Holbrook, 1838, with a new species of swamp-dwelling dusky salamander (Plethodontidae: Desmognathus) from the Atlantic Coastal Plain - Pyron, R. Alexander; Beamer, David A. (Zootaxa, 2022)
Most swamp-dwelling dusky salamanders of the genus Desmognathus from the Coastal Plain were long treated as a single species (Desmognathus auriculatus) ranging from east Texas to southeastern Virginia. This taxon concept was based on the name Salamandra auriculata Holbrook, 1838 with type locality Riceboro, Liberty County, Georgia and a type series that could not be located by later authors. Recent workers have been unable to locate or verify swamp-dwelling populations from east Texas and western Louisiana, which appear to be extirpated and may not have represented a distinct taxon from co-occurring lineages of D. conanti. Recent molecular phylogenies have supported at least four distinct species-level taxa within D. auriculatus. Populations from the Gulf Coastal Plain in eastern Louisiana, Mississippi, and southwestern Alabama were recently described as D. valentinei Means, Lamb, and Bernardo, 2017 and D. pascagoula Pyron, O’Connell, Lamb, and Beamer, 2022. This leaves two remaining species-level lineages with uncertain taxonomy and nomenclature: D. auriculatus A (Alabama, Florida, and Georgia), and D. auriculatus B/C (Georgia, South Carolina, and North Carolina), both of which occur near the type locality. We recently located a specimen at the Muséum national d’Histoire naturelle in Paris (MNHN 0.4675) that we concluded is one of Holbrook’s syntypes and designated it as the lectotype, but without allocation. Here, we use linear morphometrics to confidently allocate it to D. auriculatus A, bolstered by examination of three historical topotypic collections. This requires a new name for D. auriculatus B/C, which we describe as D. valtos sp. nov. (suggested common name: Carolina Swamp Dusky Salamander) from Otter Creek, Craven County, North Carolina. Other related and sympatric species of Desmognathus remain to be described from the Atlantic Coastal Plain and adjacent Piedmont of the southeastern United States.